Examining the Role of Resourcefulness, Market Responsiveness, and Digital Pivoting on Start-Up Resilience Post-Crisis - Sari, Tri Agriana; Ilham, Rachmad; Suroso, Adi (International Journal of Business, Law, and Education, 2025)
In the aftermath of global crises such as the COVID-19 pandemic, start-up resilience has become a central concern for entrepreneurs and scholars alike. This study investigates the roles of resourcefulness, market responsiveness, and digital pivoting in shaping the resilience of start-ups in a post-crisis environment. Drawing upon a quantitative survey of 210 start-up founders across Indonesia, data were analyzed using multiple linear regression via SPSS. The findings reveal that resourcefulness, market responsiveness, and digital pivoting each have a significant and positive effect on start-up resilience, with digital pivoting emerging as the most influential predictor. These results highlight the necessity for start-ups to foster dynamic capabilities and embrace digital transformation as strategic responses to environmental uncertainty. This study offers theoretical and practical implications for building adaptive capacity in start-up ecosystems, especially in emerging markets facing frequent disruptions.